Cost of rabies post exposure prophylaxis in different healthcare settings in six states of India - Ravish Shankaraiah Haradanhalli; Ashwath Narayana D Hanumanthaiah; Sanjay T Varadappa (Wolters Kluwer Medknow Publications, 2019)
The expenditure for rabies postexposure prophylaxis (PEP) is substantial, especially for the poor who are affected the most. The present study was conducted to determine the cost incurred to a patient and the healthcare facility for providing PEP in different healthcare settings. A multicentric, health facility-based study was conducted from May 2017 to January 2018 in the six states involving 18 healthcare facilities. The study included 529 animal bite cases; most of them belonged to either category III (54.4%) or category II (43.1%) exposures and all of them received complete PEP. The total median cost incurred to the patients for complete PEP in the government health facility was INR 1400 (USD 22) and in private hospitals was INR 3685 (USD 58). The cost of PEP for the bite victims is considerable; therefore, it has to be provided free of charge at all healthcare facilities.